2003
DOI: 10.1095/biolreprod.102.012377
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Foreign DNA Is Associated with Paternal Chromosome Degradation in Intracytoplasmic Sperm Injection-Mediated Transgenesis in the Mouse1

Abstract: The efficiency of intracytoplasmic sperm injection (ICSI)-mediated transgenesis is often limited by poor embryo development. Because our previous work indicated that impairment of embryo development is frequently related to chromosomal abnormalities, we hypothesized that foreign DNA and/or conditions used to enhance integration of the DNA might induce chromosome damage. Therefore, we examined the chromosomes of mouse embryos produced by transgenesis with the EGFP gene. Spermatozoa were processed with three met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
85
0
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(93 citation statements)
references
References 23 publications
5
85
0
3
Order By: Relevance
“…It is believed that EGTA, a calcium chelator, either prevents or decreases the activity of calcium-dependent endonucleases [14] by limiting the availability of the circulating calcium; therefore, EGTA is recommended to minimize chromosome breakage [26]. Conversely, trehalose, a disaccharide of glucose is present in many organisms that are able to survive complete dehydration, a phenomenon known as anhydrobiosis [20] and [27].…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that EGTA, a calcium chelator, either prevents or decreases the activity of calcium-dependent endonucleases [14] by limiting the availability of the circulating calcium; therefore, EGTA is recommended to minimize chromosome breakage [26]. Conversely, trehalose, a disaccharide of glucose is present in many organisms that are able to survive complete dehydration, a phenomenon known as anhydrobiosis [20] and [27].…”
Section: Discussionmentioning
confidence: 99%
“…ROS are known mostly for their detrimental effects on sperm functions (Twigg et al 1998). Szczygiel et al (2003) demonstrated that incubation of spermatozoa with exogenous DNA leads to breaks in paternal chromosomes, and it is well known that spermatozoa deficiency in nuclear DNA repair systems results in their increased susceptibility to oxidative stress and DNA fragmentation (De Lamirande et al 1997).…”
Section: F a García-vázquez And Othersmentioning
confidence: 99%
“…Factors that have been reported to influence the outcome of transgenesis in porcine embryos through ICSI include temperature during micromanipulation, exogenous DNA concentrations, plasmid constructs [3] and DNase I treatment [4] . Szczygiel et al [5] found that Ca 2+ chelators (EDTA or EGTA) in the suspensions of sperm cell and exogenous DNA could decrease transgenesis and affect the degree of DNA integration into chromosomes, and that this was related to a Ca 2+ /Mg 2+ -dependent enzyme in the oocyte. A Ca 2+ /Mg 2+ -dependent DNase I in pig MII oocytes has been documented which could significantly protect linearized exogenous DNA when microinjected [6] .…”
Section: Introductionmentioning
confidence: 99%